Dysregulated Maresin Concentrations in Plasma and Nasal Secretions From Patients With Chronic Rhinosinusitis - Beegun, Issa; Koenis, Duco S.; Alusi, Ghassan; Dalli, Jesmond (Frontiers in Immunology, 2021)
The mechanisms that lead to disease onset and propagation in patients with chronic rhinosinusitis (CRS) are not fully elucidated. Maresins (MaR) are a family of essential fatty acid-derived lipid mediators that play a central role in the regulation of inflammation with several studies demonstrating that these mediators display protective activities in airway inflammation. Therefore, in the present studies we evaluated whether concentrations of these mediators were altered in both peripheral blood and nasal secretions from CRS patients. Herein, we focused on patients with CRS that also develop nasal polyps (CRSwNP), given that therapeutic options for the treatment of these patients are limited. Thereby, insights into disease mechanisms in these patients may help design more effective treatments. For this purpose, we compared maresin concentrations from CRSwNP patients with those found in healthy volunteers or patients with a upper respiratory tract infection (URTI), as a self-resolving inflammatory condition. Using liquid chromatography tandem mass spectrometry we found that MaR concentrations were significantly decreased in plasma from patients with CRSwNP when compared to healthy volunteers. MaR concentrations were observed to be significantly upregulated in nasal secretions from patients with CRSwNP when compared with both healthy volunteers and URTI subjects. Concentration of these mediators in both plasma and nasal secretions from CRSwNP patients were positively correlated with quality-of-life scores in these patients. Assessment of the concentrations of other pro-resolving and pro-inflammatory lipid mediators (LM) demonstrated that there was a general shift in LM levels in both plasma and nasal secretions from CRSwNP when compared with healthy volunteers and URTI subjects. Of note, incubation of peripheral blood cells from CRSwNP with MaR1 downregulated the expression of activation markers on peripheral blood phagocytes, including CD41 and CD62P, markers of platelet-leukocyte heterotypic aggregates. Together these findings demonstrate that both local and systemic LM concentrations, in particularly those of the MaR family, become altered in patients with CRSwNP. They also suggest that therapeutics designed around MaR1 may be useful in regulating the activation of phagocytes in patients with CRSwNP thereby potentially also limiting the local inflammatory response in these patients.